Identification of crucial performance measurement factors affecting construction projects in Iraq during the implementation phase. Issue 1 (1st January 2021) - Zamim, Salah Kh.
Abstract: Construction industry has complexity in its nature because it contains a large number of participants as clients, consultants, contractors, stakeholders, shareholders, regulators and others. The topic of performance measurement becomes very crucial to construction projects to determine their success. Previous studies show the development of specific indicators for performance is among the most significant mechanisms for the measurement of performance. The main objective of this study is to examine and evaluate the systems for performance measurement adopted in the Iraqi construction projects during the implementation phase. This aim was achieved through structured interviews and a survey that was carried out among the different parties involved in the construction process. A total of 97 participants contributed to this survey representing public and private clients, consultants, and contractors. The analysis of the survey revealed that the most significant factors relating to the types of measurement systems in use are satisfaction of the client, the profitability of the project, viability and feasibility of the project, satisfaction of the project's users, and quality of the project. The study revealed that all of the 20 indicators suggested in the survey might be utilized to shape the performance framework measurement of Iraqi construction projects at the implementation phase.